2003
DOI: 10.3171/jns.2003.99.1.0058
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler ultrasound study of the effects of nitrous oxide on cerebral autoregulation during neurosurgical anesthesia: a randomized controlled trial

Abstract: The increase in CBF and the reduction in autoregulatory indices suggest caution in using N2O during sevoflurane anesthesia, especially in patients with reduced autoregulatory reserve and during neurosurgical interventions. Transcranial Doppler ultrasonography is an efficacious method to evaluate the effects of anesthetic agents on CBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Nevertheless, the values of the hyperaemic response recorded during sevoflurane anaesthesia were lower than those recorded in normocapnic awake patients. 11 In this study, it was recorded that when approximately 2 MAC sevoflurane concentrations were used, the hyperaemic response showed a tendency to reduce. Conversely, during propofol-remifentanil anaesthesia, the autoregulatory index increased significantly.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, the values of the hyperaemic response recorded during sevoflurane anaesthesia were lower than those recorded in normocapnic awake patients. 11 In this study, it was recorded that when approximately 2 MAC sevoflurane concentrations were used, the hyperaemic response showed a tendency to reduce. Conversely, during propofol-remifentanil anaesthesia, the autoregulatory index increased significantly.…”
Section: Discussionmentioning
confidence: 89%
“…At a concentration of 70% nitrous oxide alone does not effect a change in cerebral blood flow ; however, when used with isoflurane of halothane, both cerebral blood flow and cerebral metabolic rate increase. When added to sevoflurane, cerebral autoregulation is impaired .…”
Section: Pro – Nitrous Oxide Remains a Valuable Anesthetic For The 21mentioning
confidence: 99%
“…It is defined as the ratio between the systolic flow velocity (FV1) – calculated using the mean value of systolic peaks from five heart cycles, ending with the one preceding compression – and the hyperemic response (FV3), calculated using the mean systolic value of two heart cycles after compression, with exception of the very first cycle (Fig. 3A,B) (12, 13).…”
Section: Transcranial Dopplermentioning
confidence: 99%
“…In common with other volatile anesthetics, but in a less evident manner, sevoflurane shows an intrinsic dose‐dependent cerebral vasodilatory effect (14, 16). Several studies, in fact, have demonstrated how it increases the cerebral blood flow velocity (CBFV) and decreases the cerebrovascular resistance (CVR) in a dose‐dependent manner (13, 17, 18). The reduction of CVR could cause an impairment of cerebrovascular autoregulation mechanisms but different transient hyperemic response tests, carried out on adults and children, showed that cerebral autoregulation is well preserved during anesthesia, with up to 2.0 MAC sevoflurane (19, 20).…”
Section: Anesthetic Agentsmentioning
confidence: 99%
See 1 more Smart Citation